It is not the best option to perform transurethral enucleation of the prostate immediately after biopsy in patients with histological inflammation - Gu, Tengfei; Li, Jie; Chen, Ting; Pan, Yongtao; Sha, Jing (Frontiers in Surgery, 2024)
Objective This study seeks to investigate the impact of histopathological evidence of histological prostatic inflammation (PI) on the surgical outcomes of patients with benign prostatic hyperplasia (BPH) undergoing transurethral bipolar enucleation of the prostate (BiLEP) after biopsy. Methods We conducted a prospective study in which data were collected from 112 patients with BPH who underwent BiLEP immediately after prostate biopsy at the Department of Urology in our hospital between October 2020 and October 2023. This cohort included 52 patients with histopathological prostatic inflammation (BPH + PI group) and 60 patients with simple BPH (BPH group). Baseline characteristics, surgical details, International Prostate Symptom Score (IPSS), quality of life (QoL), post-void residual volume (PVR), maximum flow rate (Qmax), International Index of Erectile Function-5 (IIEF-5), postoperative pathology results, and surgical complications were compared between the two groups. Results The study findings indicate that in patients with BPH who underwent BiLEP, various parameters in the BPH + PI group including operation time, intraoperative flushing volume, hemoglobin drop value, postoperative white blood cells, postoperative C-reactive protein, and average pain score at 3 days postoperatively were significantly higher compared to those in the BPH group (p < 0.01). In addition, the IPSS and IIEF-5 scores of the BPH + PI group were significantly worse before surgery and at 2 weeks postoperatively compared to the BPH group (p < 0.01); however, no significant differences were observed between the two groups at 1 and 3 months postoperatively (p > 0.05). At 2 weeks postoperatively, the BPH + PI group exhibited significantly worse outcomes in terms of QoL, PVR, and Qmax compared to the BPH group (p < 0.01). However, there were no statistically significant differences between the two groups at 1 and 3 months postoperatively (p > 0.05). The incidence rates of postoperative complications, such as fever, prostatic capsule perforation, urinary tract irritation, bladder spasm, acute epididymitis, urinary tract infection, and urethral stricture, were higher in the BPH + PI group compared to the BPH group (p < 0.05). Nevertheless, there was no significant difference in the overall complication rates between the two groups (p > 0.05). There were no statistically significant differences observed between the two groups in postoperative irrigation volume, extubation time, hospitalization time, proportion of secondary operations, proportion of bladder injury, and proportion of urinary incontinence (p > 0.05). However, the proportion of reported prostate cancer after surgery in the BPH + PI group was significantly higher than that in the BPH group (p < 0.05). Conclusion Histopathological prostatic inflammation does not have a significant impact on the long-term efficacy of BiLEP surgery immediately after biopsy. However, it does prolong surgery time, increase surgery-related complications, and influence short-term surgical outcomes and patient treatment experience. Therefore, it may be advisable to administer a course of anti-inflammatory treatment before performing BiLEP in such patients. Nevertheless, further high-quality studies are necessary to validate this approach.